Clima organizacional e seus impactos – um estudo de caso em uma empresa privada que atua no setor de recursos humanos como agente de integração - Cruz, Lívia Oliveira da (Brasil, 2024)
This study investigated the influence of the organizational climate on the productivity and well-being of employees in the people management sector of a small company that acts as an integration agent. The research covered topics such as organizational climate, people management and leadership, quality of life at work and the role of an integration agent. The main objective of the study was to identify factors that influence the organizational climate and propose effective methods to improve the work environment, which through exploratory and descriptive research, using observation and semi-structured interviews with employees in the sector, it was possible to identify problems such as stress, work overload and poor communication stand out as factors that negatively affect the organizational climate, as highlighted by employees during the interview. It is noteworthy that the interview took place with the total number of employees in the sector, which totals 4 people. The observation was carried out for 5 consecutive days, monitoring the routine of employees and their activities. In this way, it was possible to propose an increase in staff and extend delivery times to reduce overload, in addition to implementing personal development workshops and visits from mental health professionals. The research also highlighted the need for continuous assessments of the organizational climate to listen to employees and promote continuous improvements.